Dye coupling of horizontal cells in the primate retina - Pan, Feng; Massey, Stephen C. (Frontiers in Ophthalmology, 2023)
In the monkey retina, there are two distinct types of axon-bearing horizontal cells, known as H1 and H2 horizontal cells (HCs). In this study, cell bodies were prelabled using 4′,6-diamidino-2-phenylindole (DAPI), and both H1 and H2 horizontal cells were filled with Neurobiotin™ to reveal their coupling, cellular details, and photoreceptor contacts. The confocal analysis of H1 and H2 HCs was used to assess the colocalization of terminal dendrites with glutamate receptors at cone pedicles. After filling H1 somas, a large coupled mosaic of H1 cells was labeled. The dendritic terminals of H1 cells contacted red/green cone pedicles, with the occasional sparse contact with blue cone pedicles observed. The H2 cells were also dye-coupled. They had larger dendritic fields and lower densities. The dendritic terminals of H2 cells preferentially contacted blue cone pedicles, but additional contacts with nearly all cones within the dendritic field were still observed. The red/green cones constitute 99% of the input to H1 HCs, whereas H2 HCs receive a more balanced input, which is composed of 58% red/green cones and 42% blue cones. These observations confirm those made in earlier studies on primate horizontal cells by Dacey and Goodchild in 1996. Both H1 and H2 HCs were axon-bearing. H1 axon terminals (H1 ATs) were independently coupled and contacted rod spherules exclusively. In contrast, the H2 axon terminals contacted cones, with some preference for blue cone pedicles, as reported by Chan and Grünert in 1998. The primate retina contains three independently coupled HC networks in the outer plexiform layer (OPL), identified as H1 and H2 somatic dendrites, and H1 ATs. At each cone pedicle, the colocalization of both H1 and H2 dendritic tips with GluA4 subunits close to the cone synaptic ribbons indicates that glutamate signaling from the cones to H1 and H2 horizontal cells is mediated by α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors.